JURGEN HABERMAS'S COMMUNICATIVE PARADIGM AS TRANSFORMATIVE DA'WAH REINFORCEMENT - Saputra, Dani (QAULAN: Journal of Islamic Communication, 2021)
Work and communication are two basic human that determine how humans as a species move and live in their world. The reformation begins with two basic human foundations. Jurgen Habermas, a German authoritarian who makes a fairly firm discount with his predecessors, seems to be in his central idea of the fundamental differences between the two dimensional praxis, namely work and communication. But it needs to be seen how communication and rationality of power are exercised, or how one positions in it. In the public space, each individual expresses his or her various thoughts related to the public interest that want to be discussed without coercion. This public space must be free from the intervention of any party, so that each individual can express his or her thoughts freely and openly. That's where a social area free from censorship and dominance. The complexity of people’s lives demands a more transformative movement of da’wah activities, in this case communication and transformative da’wah. This process also aims to "pay attention" to the target of da’wah to the weak. As coveted by the Islamic community, that not only focused on homogeneous social status, nor looked at the higher and lower social status, officials and subordinates, rich and poor, and so on. Rather, it sees from the level of laughter of an individual to his Lord. To achieve this, preachers need to emphasize an approach that better respects and respects human dignity and dignity, humanizes people, and uses local cultural approaches and the unstoppable use of information technology as a tool to transform a message.